Opposing Roles of Interferon-Gamma on Cells of the Central Nervous System in Autoimmune Neuroinflammation - Ottum, Payton A.; Arellano, Gabriel; Reyes, Lilian I.; Iruretagoyena, Mirentxu; Naves, Rodrigo (Frontiers in Immunology, 2015)
Multiple sclerosis (MS) is the principal cause of autoimmune neuroinflammation in humans, and its animal model, experimental autoimmune encephalomyelitis (EAE), is widely used to gain insight about their immunopathological mechanisms and the development of novel therapies for MS. Most studies on the role of interferon (IFN)-γ in the pathogenesis of EAE have focused on peripheral immune cells, while its action on central nervous system (CNS)-resident cells has been less explored. In addition to the well-known proinflammatory and damaging effects of IFN-γ in the CNS, evidence has also endowed this cytokine both a protective and regulatory role in autoimmune neuroinflammation. Recent investigations performed in this research field have exposed the complex role of IFN-γ in the CNS uncovering unexpected mechanisms of action that underlie these opposing activities on different CNS-resident cell types. The mechanisms behind these two-faced effects of IFN-γ depend on dose, disease stage and cell development status. Here, we will review and discuss the dual role of IFN-γ on CNS-resident cells in EAE highlighting its protective functions and the mechanisms proposed.